Experimental investigations of ultra-lightweight-concrete encased cold-formed steel structures: local stability behavior of C-section profiles subjected to eccentric compression - Alabedi, Ahmed; Hegyi, Péter (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Nowadays, cold-formed steel (CFS) has become widely used in the field of lightweight structures. In 2016, the Budapest University of Technology and Economics initiated a research study on a unique structural system using CFS and utilized ultra-lightweight concrete as an encasing material. This material serves as continuous bracing that improves CFS element resistance, stability behavior and performance, while also manifesting heat insulation capabilities, thus helping achieve sustainability goals. This paper is considered a continuation of previous research conducted by the authors. An experimental investigation was carried out on encased CFS columns subjected to eccentric loading. A total of fourteen stub-columns, with two distinct thicknesses, were subjected to various loading conditions for testing. The test results showed that local failure controlled the behavior of all the tested elements. The reduction in capacity resulting from eccentricity with respect to centric resistance varied between 20% and 52%, depending on the load position applied and on the core thickness of the tested steel elements. Moreover, the test outcomes were compared to the Eurocode analytical solution of pure steel elements. The overall load increment ranged from 46% to 18%, with a more noticeable bracing impact observed in the case of slender elements. Material tests also supplement the results.